Influence of Occupational Therapy at Home to Upper Extremity Function and Activities of Daily Living on Hemiplegia Patients with Stroke in Middle-late Stages - Yan CHEN; Shaohui ZHANG; Ye CHEN (康复学报)
Objective:To discuss the effects of occupational therapy at home to upper extremity function and activities of daily living (ADL) on hemiplegia patients with stroke in middle-late stages.Methods:Seventy-four hemiplegia patients with stroke in middle-late stages were randomly divided into the experimental group (38 cases) and control group (36 cases). There were no significant differences between the two groups in the age, gender, the course, simplify Fugl-Meyer and Barthel index. Both of the two groups accepted routine medicine therapy. The experimental group accepted occupational therapy at home and the control group did not accept occupational therapy at home. Fugl-Meyer assessment of upper extremity function and Barthel index were measured separately in the beginning and the later three months in the two groups.Results:After three months of treatment, significant difference was found in upper extremity function and Barthel index between the two groups (P<0.01).Conclusion:The good promoter action has been seen in the post-stroke hemiplegia patients in middle-late stages with the occupational therapy at home to upper extremity function and activities of daily living.